Identifikasi Pola Makan dan Skrining Status Gizi Anak Sekolah di SDN 129 Palembang - Febry, Fatmalina; Misnaniarti, Misnaniarti; Ainy, Asmaripa; Etrawati, Fenny; Maulina Sari, Desri (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: Primary school children need adequate nutrition to avoid deviations in growth and development. The imbalance between intake and nutritional adequacy will cause nutritional problems. This activity aims to determine elementary school children's diet, nutritional status, and knowledge about balanced nutrition. Methods: This service activity is integrated with the Food Consumption Assessment course of Nutrition Study Program students of the Faculty of Public Health Semester V. This activity participants were 5th-grade students of State Elementary School 129 Palembang, totaling 53 people. This activity was carried out in 3 stages: nutritional status screening, interviews related to food intake, and nutrition education. Results: Most of the students had underweight status 81.1% (weight-for-age) and normal nutritional status 69.8% (height-for-age) and 62.3% (BMI-for-age). Most students consumed incomplete meals (79.2%) and a deficit energy adequacy level (67.9%). There was an increase in knowledge at pretest (28.3%) and posttest (56.6%). Conclusion: There is an increase in student knowledge after being given education in the form of lectures and educational games with an additional average score of 8.49 points.